Applications of Artificial Intelligence in Banking and Financial Services - Amal Joseph (AG Volumes, 2023)
The integration of Artificial Intelligence (AI) technology has brought about a significant revolution in the banking and financial services sector. This chapter presents a comprehensive overview of the profound influence of artificial intelligence (AI) in the domain of banking and financial services. The utilisation of artificial intelligence (AI) in the fields of finance and banking has initiated a paradigm shift, bringing about a period of significant transformation for the industry. AI technologies have facilitated the improvement of client experiences, operational efficiency, and decision-making capabilities within institutions. Artificial intelligence (AI) is playing a pivotal role in enhancing efficiency, precision, and advancement within the financial services sector. Its applications span across various areas such as fraud detection, risk assessment, algorithmic trading, and chatbot development.